Wisata Gastronomi Sebagai Daya Tarik Destinasi di Surabaya - Tevila Akwila; Vanny Chang Nurmanto; Asep Parantika (Peneliti.net, 2023)
Initiation of the Central Government by designating Surabaya as one of the cities that accelerates its development through culinary and shopping tourism, thereby strengthening its position and potential as a creative city. Gastronomic tourism is another way to enjoy tourist attractions and preserve culture in the culinary field. From the product aspect of culinary tourism destinations, Surabaya has unique products and a variety of culinary preparations. This research was conducted to get an overview of the feasibility of the city of Surabaya as gastronomic tourism. The research method used is a qualitative approach with data collection carried out by observation and in-depth interviews. Based on the results of the study it can be concluded that Surabaya is quite ready to become a gastronomic tour but of course, it must be developed so that it can become a tourist attraction, efforts that can be made to develop gastronomy in Surabaya such as material readiness, cleanliness of the place, food presentation as well as product quality and meaning from the food served which can be added value to tourists and the people in Surabaya.